The assembly, biogeography and co-occurrence of abundant and rare microbial communities in a karst river - Wu, Yongjie; Zhang, Yang; Fang, Huaiyang; Wang, Cheng; Wang, Zengrui; Zhang, Wucai; Mai, Bixian; He, Zhili; Wu, Renren; Li, Kaiming (Frontiers in Marine Science, 2023)
Karst rivers are highly susceptible to environmental disturbance due to their robust hydraulic connectivity. However, current knowledge of the mechanisms that regulate the assembly of bacterial and protistan subcommunities in river ecosystems, particularly in karst regions, is limited. By employing 16S and 18S rRNA gene amplicon sequencing, we explored how the diversities and assembly of abundant and rare bacterial and protistan subcommunities adapt to the local environmental variables in a karst river. Both bacterial and protistan rare subcommunities in karst river environments showed a similar biogeography to their abundant subcommunities. Also, a significant distance-decay pattern was observed in all components of the bacterial and protistan subcommunities along the Chishui River, with the rare subcommunities showing a more pronounced distance-decay pattern compared to the abundant subcommunities. Except protist rare subcommunity, the abundant and rare bacterial and abundant protistan subcommunities were strongly structured by the dispersal limitation processes rather than heterogeneous selection. Either bacteria or temperature, elevation and conductivity were the primary drivers for both abundant and rare subcommunities. Additionally, our results suggested that the rare subcommunities contribute significantly to the persistence and stability of microbial networks in the Chishui River, as they exhibited a higher number of keystones compared to the abundant subcommunities. Overall, our study revealed that in the karst river ecosystem, abundant bacterial subcommunities had a higher potential for environmental adaptation than rare bacterial and protistan subcommunities and identified the factors that moderate their assembly processes.